Shifting sands: The reconfiguration of neoliberal youth penality - Gray, Patricia (Theoretical criminology, 2021)
This article begins by tracing the emergence of ‘therapeutic surveillance’ as a new formula for neoliberal disciplinary power. It maps and interrogates the reconfiguration of a hybrid array of neoliberal rationalities and technologies for the penal governance of young people who offend. It then engages with the challenges posed by critical realists to the governmentality position by questioning how human agency can contest, subvert and resist the dystopian reach of ‘therapeutic surveillance’ in action. While ‘therapeutic surveillance’ is steeped in a disciplinary logic of individualization and responsibilization, we argue that it also opens the space for a more transformative youth penality to be articulated; one which challenges the constraints of structural disadvantage in the pursuit of social justice. The article concludes by arguing that newly emerging youth justice configurations which have appeared in response to dramatic cuts in public spending offer a plausible or transformative challenge to the regulatory logic of neoliberal youth penality.